Medical professional image in the social media by Muscovites: managerial and methodological aspects - I. V. Bogdan; A. A. Dreneva; D. P. Chistyakova (Цифровая социология, 2022)
The article presents a comparative study of social perception of a medical professional in the mass consciousness using social media monitoring and telephone survey. The aim of the study is to develop methodological recommendations for analysis and information policy on the formation of the medical professional image in the mass consciousness. The basis of the study is a sample of posts published by Muscovites in social media containing keywords associated with physician and nurses. In addition, another survey on people’s associations with these professions was conducted in order to compare the image in social media to the image held in the mass consciousness. The authors manually coded subsample of the respondents’ posts and articles from social media. The authors’ Python code was additionally used to analyse figures and lemmas. The study has allowed to describe the main elements of the specialists’ image among the population, including the perception of “typical” physical characteristics for a health care worker, professional and personal qualities, and the relationship between the image of a physician and a nurse, where the former usually has a higher status than the latter. The study has revealed similar characteristics, but their different quantitative representation in the survey and analysis of social media, which has allowed to recommend social media analysis for performing qualitative analysis of the population’s opinions. At the same time, quantitative monitoring of the image in the online environment is also seen as useful due to the significant influence of social media on the formation of opinions in the mass consciousness. Such monitoring may be used as a way to get feedback within the framework of the image formation management process.